Hisse Senetleri Fiyatlarının Belirlenmesinde Finansal Oranların Rolü(The Role of Financial Ratios in Determining the Stock Prices) - Oğuzhan AYDEMİR; Serdar ÖGEL; Gökhan DEMİRTAŞ (Yönetim ve Ekonomi, 2012)
In this study, financial ratios being effective in determining stock prices are investigated by panel data analysis. In this aim, data set belonging to 73 companies indexed in Istanbul Stock Exchange (ISE) and operating in manufacturing sector over the period of 1990-2000 is used. Empirical results suggest that profitability and liquidity ratios have a positive effect on stock returns. Moreover, leverage ratio taken as an indicator of indebtedness has the same effect. However, it is seen that operating ratios have no impact on stock returns. Consequently, it may be said that the role of financial ratios in determining the stock returns is low.